A serum metabolomics‐driven approach predicts orange juice consumption and its impact on oxidative stress and inflammation in subjects from the BIONAOS study. Issue 2 (9th December 2016) - Rangel‐Huerta, Oscar D.; Aguilera, Concepcion M.; Perez‐de‐la‐Cruz, Antonio; Vallejo, Fernando; Tomas‐Barberan, Francisco; Gil, Angel; Mesa, Maria D.
Abstract : Using an untargeted metabolomics analysis a new panel of biomarkers able to identify orange juice consumption is designed. Likewise, it is described that the consumption of orange juice with a high content of flavanones improves oxidative stress and inflammatory biomarkers. Abstract : Scope: To identify biomarkers of orange juice (OJ) consumption containing different doses of polyphenols and to determine its impact on oxidative stress and inflammation using an untargeted metabolomics analysis. Methods and results: Thirty subjects aged 22–63 years from the BIONAOS study consumed a normal‐polyphenol OJ (NPJ) or a high‐polyphenol OJ (HPJ) (299 or 745 mg/L, respectively) for 12 weeks in a randomized, parallel, double‐blind study. UHPLC‐MS, univariate and multivariate statistical analysis and ROC curves were used to design biomarkers of consumption in serum. We propose betonicine, stachydrine, methyl glucopyranoside (alpha+beta), dihydroferulic acid and galactonate as a new metabolic signature to distinguish the intake of OJ with a different polyphenol content. Changes in metabolites related to OJ, oxidative stress and inflammation were observed. After HPJ consumption, the serum levels of hydroxyoctadecadienoic acid (9‐HODE+13‐HODE) and dihydroxyoctadecanoic acid (12, 13‐DiHOME and 9, 10‐DiHOME) decreased, whereas levels of 12‐hydroxyeicosatetraenoic acid (12‐HETE) increased. 5‐HETE increased after the NPJ intervention exclusively. Conclusion: We designed a new panel of biomarkers to differentiate the intake of OJs containing different doses of polyphenols. On the other hand, the consumption of an OJ with a high content of flavanones improved oxidative stress and inflammatory biomarkers.